Perovskite-Based Triboelectric Nanogenerator and Its Application Towards Self-Powered Devices - Zhangsiyuan Jin; Hening Xing; Yian Hu; Yuljae Cho (Nanoenergy Advances)
Research on triboelectric nanogenerators (TENGs) and self-powered devices has rapidly grown in recent years since its first report in 2012 by Prof. Wang’s group. Triboelectric polymers have been a frontier of the research, attributed to their high surface potential and consequently high voltage output. To further advance the field, in recent years, photoactive semiconductor materials have been introduced which offer an additional current generation mechanism under light excitation, boosting the output current of the TENG. In addition, the semiconductor-based TENG further provides an ability to detect photo-signals beyond mechanical signals, adding high value towards advanced multi-functional sensor applications. In this regard, this article aims to review the recent progress in semiconductor-based TENGs, particularly on metal-halide perovskites, and their applications to self-powered electronics. Finally, the prospects and challenges of the perovskite-based TENG are discussed.